SEISMICALLY INDUCED VARIATIONS IN MARIÁNSKÉ LÁZNě FAULT GAS COMPOSITION IN THE NW BOHEMIAN SWARM QUAKE REGION, CZECH REPUBLIC - A CONTINUOUS GAS MONITORING - Weinlich F.H.; Faber E.; Teschner M.; Poggenburg J.; Boušková A.; Horálek J. (My University, 2006)
A continuously operated gas monitoring station was emplaced within the epicentral area of the NW Bohemian swarm earthquakes overlying directly the active Mariánské Lázně fault. The recordings of 8-month continuous monitoring period are presented. The variations in radon concentrations are similarly to variations in CO2, i.e. CO2 is considered to be the carrier gas for radon. Very small diurnal variations in gas concentration are caused by the earth tides, as daily variations in meteorological conditions cannot explain a short daily minimum at midday times. Sudden changes in gas concentration, which clearly exceed these diurnal variations occur and are always linked with seismic activities. Decreased gas concentration may indicate compression resulting in reduced fault permeability as is implied by negative peaks following local earthquake swarms. A sudden increase in CO2 and Rn concentration may indicate an increased fault permeability caused by stress redistribution, giving rise to opening of migration pathways. This implies a repeatedly sudden rise in gas concentration before local earthquake swarms. Several variations in gas concentration were monitored linked with remote earthquakes of ground motion amplitudes >1 μm. These seismic events are accompanied by an interference of the diurnal gas concentration–stress-cycle along the Mariánské Lázně fault. However, if shocks of remote earthquake can alter properties of the migrating fluids or the fault properties it can be suggested that these are able to trigger local seismicity, as indicated in the case of the Slovenia earthquake on 12th July 2004.